Marketing plan to increase LG’STV product category premium perception by end consumers: product and pricing strategy for LG - Steinmann, Viola (2022)
LG offers both TVs at lower price points and high-end TVs, such as its OLED lines, which will be the focus of this report. As part of the marketing mix strategy to increase LG’s premium perception, this paper will elaborate on the product and pricing strategies, based on discussions of primary and secondary research .A value-based pricing approach was applied, and a product offering was created with the focus on refining the entire customer experience.